The life of Sir Hersch Lauterpacht, QC, FBA, LLD / by Elihu Lauterpacht. - Lauterpacht, Elihu (Cambridge University Press, 2010)
Hersch Lauterpacht, of whom this book is an intimate biography by his son, Elihu, was one of the most prolific and influential international lawyers of the first half of the twentieth century. Having come to England from Austria in the early 1920s, he first researched and taught at the London School of Economics before moving to Cambridge in 1937 to become Whewell Professor of International Law. He did valuable work to enhance relations with the United States during the Second World War and was active after the war in the prosecution of William Joyce and the major Nazi war criminals. For ten years he was also involved in various significant items of professional work and in 1955 he was elected a judge of the International Court of Justice. The book contains many extracts from his correspondence, the interest of which will extend to lawyers, historians of the period and beyond.